Inhibition of Prostate Cancer (LNCaP) Cell Proliferation by Volatile Components from Nagami Kumquats - Jayaprakasha, Guddadarangavvanahally K.; Murthy, Kotamballi N. Chidambara; Demarais, Rock; Patil, Bhimanagouda S. (Planta Medica, 2012)
Fresh Nagami kumquats (Fortunella margarita) were subjected to hydrodistillation using a Clevenger-type apparatus to obtain volatile oil. The chemical composition of the volatile oil was analyzed by GC-MS using Rtx-5 Sil MS and DB Wax columns. A total of 25 volatile compounds were identified by mass spectra, retention index, and comparison with known standards. The major identified compounds are d-limonene (41.64 %), β-myrecene (16.54 %), linalyl propionate (9.55 %), and germacrene-D (5.93 %) from the Rtx-5 Sil MS column; d-limonene and β-myrecene were also separated as major compounds on the DB wax column. The oil is rich in hydrocarbons (77.41 %) consisting of 60.05 % monoterpenes and 17.36 % sesquiterpenes. Interestingly, oxygenated hydrocarbons (17.6 %) were also found in kumquat volatile oil. Certain volatile compounds were also confirmed by positive chemical ionization and NMR spectra. Further, the volatile oil demonstrated good DPPH radical scavenging activity and antioxidant capacity. Kumquat volatile oil at 200 ppm concentration exhibited 55 %, 61 %, and 63.4 % inhibition of human prostate cancer (LNCaP) cell proliferation at 24, 48, and 72 h, respectively, by cell count assays. Significant increases in expression of bax/bcl2 and p53 proteins confirmed that volatile oil induces apoptosis. In addition, inhibition of inflammatory markers such as NF-κB and Cox-2 was observed. The cleavage of caspase-8 in the LNCaP cells treated with volatile oil demonstrated that apoptosis occurred through an extrinsic pathway. This is the first report of the identification and possible mechanisms of in vitro antiproliferative effects of kumquat volatile components on human prostate cancer (LNCaP) cells.
Keywords: Fortunella margarita Swingle; Rutaceae; d-limonene; ABTS; LNCaP cells; apoptosis